Path Analysis on the Risk Factors of Sexually Transmitted Disease among Men Who Have Sex with Men Community in Surakarta - Siti Nurhalimah; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Men who have sex with men (MSM) have a higher prevalence of HIV and other sexually transmitted infections (STI) than the heterosexual men. The number of STI cases in MSM in Indonesia in 2017 was 4,144. The study aimed to examine risk factors of sexually transmitted disease among MSM community in Surakarta, Central Java.Subjects and Method: This was a cross-sectional study carried out in Surakarta, Central Java, from October to November 2018. A sample of 188 MSM was selected by fixed diseases sampling. The variable dependent was STI. The independent variables were age, education, number of sexual partners, sexual behavior, intention, attitude, perceived behavior control, and subjective norm. The data were collected by questionnaire and analyzed by path analysis.Results: STI was directly increased by unsafe sexual behavior (b= 2.03; 95% CI= 1.15 to 2.91; p<0.001), older age (b= 1.83; 95% CI= 0.58 to 3.09; p= 0.004), multiple sexual partners (b= 2.28; 95% CI= 1.33 to 3.23; p<0.001). It was indirectly affected by intention, attitude, perceived behavior control, subjective norm, and education.Conclusion: STI is directly increased by sexual behavior, age, multiple sexual partners. It is indirectly affected by intention, attitude, perceived behavior control, subjective norm, and education.Keywords: sexually transmitted infections, sexual behavior, men who have sex with menCorrespondence: Siti Nurhalimah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: halimah1006.mdf@gmail.com. Mobile: 082233890866. Journal of Health Promotion and Behavior (2018), 3(3): 199-211https://doi.org/10.26911/thejhpb.2018.03.03.07